Influence of wetting fluids on the compressive strength, physicochemical, and pore-structure evolution in lime-treated silty soil subjected to wetting and drying cycles. (July 2022) - Das, Geetanjali; Razakamanantsoa, Andry; Herrier, Gontran; Deneele, Dimitri
Highlights: Effect of the nature of wetting fluids on compacted lime-treated soil is investigated. Lime-treated soil is submitted to wetting-drying cycles using different liquids. Unconfined compressive strength increased irrespective of the nature of wetting fluids. Extent of compressive strength increased varies by the nature of subjected wetting fluids. Extent of chemical and pore-structure evolution varies by the nature of subjected wetting fluids. Abstract: The long-term benefit brought in lime-treated soil can be altered by the nature of the surrounding wetting fluid, thus, affecting its durability. However, studies regarding such impact are limited. In this study, the influence of different wetting fluids on the microstructural, physicochemical modifications, and Unconfined Compressive Strength (UCS) evolution of lime-treated soil is investigated. Lime-treated soils are subjected to wetting and drying cycles using 0.10 M and 0.60 M NaCl solutions, demineralized water, and Methyl Methacrylate. The results show that despite the soil being exposed to several wetting and drying cycles, the UCS evolved positively compared to the reference specimen. However, this evolution varies with the types of wetting fluids the specimens are exposed to. The NaCls-and Methyl Methacrylate-subjected soils showed an increase in UCS up to about 3 times, while the UCS increase is about 2 times in the corresponding demineralized water subjected soil. Similarly, the extent of the variation of the final pH and the cumulative calcium concentrations measured in the effluent is marked by the wetting fluids available in the surrounding medium. At the pore structure level, the presence of NaCl solutions and Methyl Methacrylate solvent as a wetting fluid was observed to enhance the evolution of pores smaller than 3000 Å. However, such a phenomenon is less significant in the demineralized water-subjected soil. Thus, the study confirms that the type of wetting fluid plays an important role in the evolution of lime-treated soil during the wetting and drying cycles.